Analysis of vibration signals related to fuel tank in a passenger coach [Bi̇r yolcu otobüsünün yakit deposununa i̇li̇şki̇n ti̇treşi̇m si̇nyalleri̇ ni̇n anali̇zi̇] - (:unkn) unknown (My University, 2008)
In this study, the data which was taken from accelerometer located in vertical direction to fuel tank chassis of a traveler bus has been analyzed. Firstly vibration signal related to the endurance of the connection has been observed as a raw data on the time-frequency plane and then it has been passed from a critical frequency 20 Hz low pass filter and power spectrum changes have been observed. After this, critical frequency value whose peak value is about 11 Hz has been forced mechanically to the construction which consists of fuel tank has been determined. In addition, it was determined that 11 Hz emerged at about 244th second on the time scale and it has been observed that big amplitude has also been created by this frequency on the time serial. ©2008 IEEE.